Dobry molodtsy . Dobry molodtsy . Fine Fellows . Добры молодцы - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The program for young men, discussing such topics as plastic surgery; motorcycles; advice on making acquaintance with women. Программа для молодых мужчин, обсуждающая такие темы как пластическая хирургия, мотоциклы; советы по знакомству с девушками.